2016
DOI: 10.1155/2016/3752484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on the HDS Activity of Molybdenum Sulfide

Abstract: More than half of the total world oil reserves are heavy oil, extra heavy oil, and bitumen; however their catalytic conversion to more valuable products is challenging. The use of submicronic particles or nanoparticles of catalysts suspended in the feedstock may be a viable alternative to the conversion of heavy oils at refinery level or downhole (in situ upgrading). In the present work, molybdenum sulfide (MoS2) particles with varying diameters (10000–10 nm) were prepared using polyvinylpyrrolidone as capping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Thus, Ye et al [8] synthesized NiMoO 2 S 2 nanoparticles (13 nm) using a microemulsion system, and the particles were tested as lubricant. FeMo and NiMo sulfide particles (400-600 nm and 30-100 nm) have been prepared [9,10] by thermal decomposition of emulsions, and tested in HDS of Thiophene or Vacuum Gas Oil. Also, using ultrasonic irradiation, NiMo and CoMo sulfide particles (250-500 nm) were synthesized and tested in the HDS of Thiophene and Benzothiophene [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Ye et al [8] synthesized NiMoO 2 S 2 nanoparticles (13 nm) using a microemulsion system, and the particles were tested as lubricant. FeMo and NiMo sulfide particles (400-600 nm and 30-100 nm) have been prepared [9,10] by thermal decomposition of emulsions, and tested in HDS of Thiophene or Vacuum Gas Oil. Also, using ultrasonic irradiation, NiMo and CoMo sulfide particles (250-500 nm) were synthesized and tested in the HDS of Thiophene and Benzothiophene [11].…”
Section: Introductionmentioning
confidence: 99%
“…This may be induced by the addition of the acid and, what is more, the formation of MoS 3 particles. Contreras and co-workers 45 put forward that the acidification of ATTM could endow the material with a large surface area in the presence of polyvinylpyrrolidone. In this experiment, although no template was added, the aggregation of MoS 3 particles was inhibited by the pore structures of Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…From these results one can concluded that co-catalyst 1 exhibited a best morphological surfaces and smallest particle size, while the other ratio and dual oxide spinel gives large particles size. All these particle size which lie in the meso region will be efficient and can improve catalytic activity of the used catalyst [24].…”
Section: Resultsmentioning
confidence: 99%